Users and Services of General Energy Interest - Rodríguez-Arana Muñoz, Jaime (2015)
Modern Administrative Law must be considered within the Social and Democratic Rule of Law. Citizens, as users of services of general interest, are at the centre of all the categories of Regulatory Law. They have a legal status that enables them to be present in the decisions that affect them and they can contest decisions that harm their rights.